Multilayer composite infrared shielding fabric based on graphite powder and preparation method thereof

By doping antimony and tin into graphite powder and combining multi-layer composite structures and aerogel film, the problem of unsatisfactory bonding fastness in the surface coating of existing stealth textiles is solved, and efficient far-infrared shielding and thermal insulation effect is achieved, enhancing the stealth function of the fabric.

CN119800698APending Publication Date: 2025-04-11QINGDAO XUEDA GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411979756.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The surface coating of existing stealth textiles has a poor bonding fastness to the fabric, which is prone to erosion and fall off, affecting its infrared stealth function.

Method used

Graphite powder is used to co-calcinate with tin source and antimony source, and dopant antimony and tin to improve the far-infrared absorption and shielding effect of the powder, and achieve double-layer shielding and heat insulation effect through the combination of multi-layer composite structure and aerogel film.

Benefits of technology

It significantly improves the far-infrared shielding effect and thermal insulation performance of the fabric, reduces the infrared reflectivity, enhances the stealth function of the fabric, and reduces the process cost.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a multi-layer composite infrared shielding fabric based on graphite powder and a preparation method of the multi-layer composite infrared shielding fabric, and relates to the technical field of wave-absorbing fabrics. Graphite powder, a tin source and an antimony source are calcined together, the far infrared absorption and shielding effects of the powder are improved, the powder serves as a color paste raw material and a gel raw material to participate in polyester fiber spinning and surface aerogel film establishment, the double-layer shielding effect is achieved, and the far infrared effect of the fabric is greatly improved. The low-infrared-reflectivity dye and the shielding filler are optimized and compounded into the color paste with a certain concentration, and the color paste and the polyester are continuously regulated and controlled to a proper proportion, so that far infrared rays in a certain wavelength range can be absorbed to the greatest extent, the far infrared emissivity is effectively reduced, and the low-infrared-reflectivity far-infrared fabric can be used for military stealth clothing. The aerogel film adopts the shielding filler and the silica sol as raw materials, far infrared shielding is achieved, meanwhile, the shielding filler and the silica aerogel act together to improve the heat insulation performance of the aerogel film, and the thermal infrared camouflage effect of the fabric is further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wave-absorbing fabrics, in particular to a multi-layer composite infrared shielding fabric based on graphite powder and a preparation method thereof. Background Art

[0002] In recent years, with the advent of various advanced detection technologies and precision-guided weapons, the threats to military targets, weapons and equipment, and combat soldiers on the battlefield have become increasingly serious. As an important means to improve the survivability of weapons and equipment in war, stealth technology has received increasing attention from countries around the world.

[0003] According to different detection technologies, stealth technology can be divided into radar stealth, infrared stealth, laser stealth, acoustic stealth and visible light stealth. At present, radar detection accounts for about 60% of military detection, infrared detection accounts for 30%, and other 10%. Therefore, the current stealth technology research is mainly based on radar and infrared stealth, supplemented by visible light and acoustic wave stealth.

[0004] With the rapid development of infrared detection technology, infrared low-detectable technology (infrared stealth) as a means of counter-reconnaissance has attracted the attention of the military and scientific and technical personnel. The feasibility of infrared stealth comes from Stefan Boltzmann's law. Any object above absolute zero will emit infrared radiation and conform to Stefan Boltzmann's law. Infrared thermal imaging is formed by the infrared radiation contrast between the target and the background. Therefore, reducing the surface temperature and infrared emissivity of the object is the main means to achieve infrared stealth.

[0005] At present, the preparation of stealth textiles is mainly based on coating finishing production. This method is greatly affected by the bonding strength between the surface stealth coating and the fabric. Especially for stealth textiles with multi-layer coatings, the bonding strength between the coating and the fabric and between the coatings is not ideal, and the surface coating is easily corroded or even falls off, which has a huge impact on the stealth function of the fabric. Summary of the invention

[0006] The object of the present invention is to provide a multi-layer composite infrared shielding fabric based on graphite powder and a preparation method thereof, so as to solve the problems existing in the prior art.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a multi-layer composite infrared shielding fabric based on graphite powder, comprising a shielding fabric and a heat-insulating aerogel film, wherein the shielding fabric is made by melt spinning and weaving colored polyester masterbatch at 265-290°C;

[0008] The preparation method of the colored polyester masterbatch is:

[0009] (1) Graphite powder, antimony sulfide, stannous chloride pentahydrate, deionized water, and ethylene glycol are mixed in a mass ratio of 10-12:0.5-1:0.5-2:6:4, ground at 80°C for 4-5 hours, heated to 160-220°C, dried for 10-16 hours, and then calcined at 550°C for 4-6 hours to obtain antimony-tin-doped graphite powder;

[0010] (2) by weight, 5 to 10 parts of antimony-tin-doped graphite powder, 5 to 10 parts of iron oxide green, 10 to 15 parts of phthalocyanine green, 10 to 15 parts of chromium oxide green, 20 to 40 parts of polyvinyl pyrrolidone, 10 to 15 parts of sodium lignin sulfonate, 2 to 8 parts of thickener, 1 to 5 parts of defoamer, 3 to 8 parts of ethylene glycol, and 50 to 60 parts of deionized water are stirred and dispersed uniformly, injected into a ceramic nano-grinder for vacuum grinding, and the grinding is stopped when the particle size reaches 200 nm to obtain a color paste;

[0011] (3) The color paste and polyester chips are mixed in a mass ratio of 1:3-11, kneaded at 170-230° C., and then extruded and granulated at 190-280° C. and a rotation speed of 120-380 rpm to obtain a colored resin masterbatch.

[0012] Furthermore, the grinding speed in step (1) is 100 rpm-500 rpm, and the mass ratio of the grinding balls to the mass of the silicon graphite powder is (5-20):1.

[0013] Furthermore, the grinding jar and grinding balls used are made of the same material, which is stainless steel, hard steel, zirconia ceramics, corundum or agate.

[0014] Furthermore, the thickener in step (2) is an acrylate polymer, and the defoaming agent is a non-ionic multiphase silicone polymer.

[0015] Furthermore, the shielding fabric has a grammage of 180 to 220 g / m 2 .

[0016] Furthermore, the preparation method of the thermal insulation aerogel film is as follows: antimony-doped tin graphite powder and concentrated sulfuric acid are mixed, heated and acidified, and then filtered and washed repeatedly with deionized water until the pH of the supernatant is 5-6, and then freeze-dried to obtain acidified antimony-doped tin graphite powder; ethyl orthosilicate, anhydrous ethanol, deionized water, N, N-dimethylformamide, and oxalic acid are mixed, and 1 / 2 of the acidified antimony-doped tin graphite powder is added in a ratio of 1-3g:10mL. After mixing evenly, the fabric is soaked therein, and after soaking for 12 hours, the pH is adjusted to 8 with ammonia water with pH=12, and the fabric is allowed to stand at 50°C for 24 hours, and the fabric is taken out, and the anhydrous ethanol is replaced with deionized water, and then it is continued to be soaked in deionized water, and the remaining 1 / 2 of the acidified antimony-doped tin graphite powder is added, and it is allowed to stand for 24 hours, taken out, and obtained by freeze-drying.

[0017] Furthermore, the ratio of the antimony-tin-doped graphite powder to concentrated sulfuric acid is (3-5) g: (30-50) mL.

[0018] Furthermore, the molar ratio of the tetraethyl orthosilicate, anhydrous ethanol, deionized water, N,N-dimethylformamide, and oxalic acid is 1:6-10:3-5:1-2:8×10 -5 .

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] (1) The present invention adopts graphite powder and tin source and antimony source to be calcined together to achieve antimony and tin doping in the graphite structure, thereby improving the far-infrared absorption and shielding effect of the powder and reducing the infrared reflection effect, thereby promoting the optimization of the far-infrared shielding effect of the fabric. At the same time, the doping of antimony and tin can greatly improve its dispersibility in color paste and silica sol, without the need for additional surface pretreatment steps, thereby reducing the process cost. It is used as the color paste raw material and gel raw material to participate in the spinning of polyester fibers and the establishment of surface aerogel film, thereby achieving a double-layer shielding effect and greatly improving the far-infrared effect of the fabric. Due to the good dispersibility of the filler, the antimony-tin-doped graphite powder combined with the base material, especially the silica sol, can form a three-dimensional thermal insulation network, effectively optimize the thermal insulation performance of the fabric, thereby driving the low infrared reflection of the fabric.

[0021] (2) The present invention uses low infrared reflectivity dyes and shielding fillers to optimize and compound into a color paste of a certain concentration, and continuously adjusts the ratio with polyester to a suitable level, which can absorb far infrared rays within a certain wavelength range to the maximum extent, effectively reducing the far infrared emissivity, and can be used in military stealth clothing to expand the use of fabrics.

[0022] (3) The aerogel film of the present invention uses shielding fillers and silica sol as raw materials. While achieving far-infrared shielding, the shielding fillers have a heat-insulating effect, and the bubbles of the aerogel can play a role in blocking heat transfer. The two work together to improve the heat-insulating performance of the aerogel film. The heat of the target created by the present invention will not be transferred outward, and the far-infrared energy emitted by the human body can be effectively attenuated. After night-time testing with a thermal infrared imager, the human body image disappears after the human body is camouflaged, further enhancing the thermal infrared camouflage effect of the fabric. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] A multi-layer composite infrared shielding fabric based on graphite powder, comprising a shielding fabric and a heat-insulating aerogel film, wherein the shielding fabric is made of colored polyester masterbatch melt-spun at 265-290°C and woven to obtain a gram weight of 180 g / m 2 ;

[0026] The preparation method of the colored polyester masterbatch is:

[0027] (1) Graphite powder, antimony sulfide, stannous chloride pentahydrate, deionized water, and ethylene glycol are mixed in a mass ratio of 10:0.5:0.5:6:4, ground at 80°C for 4-5 hours, heated to 160°C, dried for 10 hours, and then calcined at 550°C for 4 hours to obtain antimony-tin-doped graphite powder; the grinding speed is 500 rpm, and the mass ratio of the grinding ball to the mass of the silicon graphite powder is 10:1;

[0028] (2) by weight, 5 parts of antimony-tin-doped graphite powder, 5 parts of iron oxide green, 10 parts of phthalocyanine green, 10 parts of chromium oxide green, 20 parts of polyvinyl pyrrolidone, 10 parts of sodium lignin sulfonate, 2 parts of thickener, 1 part of defoamer, 3 parts of ethylene glycol, and 50 parts of deionized water were stirred and dispersed uniformly, injected into a ceramic nano-grinder for vacuum grinding, and the grinding was stopped when the particle size reached 200 nm to obtain a color paste;

[0029] (3) mixing the color paste and polyester chips in a mass ratio of 1:5, kneading at 170-230° C., and then extruding and granulating at 190-280° C. and a rotation speed of 120-380 rpm to obtain a colored resin masterbatch;

[0030] The preparation method of the thermal insulation aerogel film is as follows: antimony-doped tin graphite powder and concentrated sulfuric acid are mixed at a ratio of 3 g:30 mL, stirred continuously in a water bath at 80° C. for 4 h, filtered and washed repeatedly with deionized water until the pH of the supernatant is 5.5, and then freeze-dried to obtain acidified antimony-doped tin graphite powder; tetraethyl orthosilicate, anhydrous ethanol, deionized water, N,N-dimethylformamide, and oxalic acid are mixed at a molar ratio of 1:7:3:1 to 8×10 -5 Mix, add 1 / 2 of the acidified antimony-tin-doped graphite powder in a ratio of 1g:10mL, mix evenly, soak the fabric in it, soak for 12 hours, adjust the pH to 8 with ammonia water with pH=12, let it stand at 50°C for 24 hours, take out the fabric, replace the anhydrous ethanol with deionized water, continue to soak it in deionized water, add the remaining 1 / 2 of the acidified antimony-tin-doped graphite powder, let it stand for 24 hours, take it out, and obtain it through freeze-drying.

[0031] Example 2

[0032] A multi-layer composite infrared shielding fabric based on graphite powder, comprising a shielding fabric and a heat-insulating aerogel film, wherein the shielding fabric is made by melt spinning and weaving colored polyester masterbatch at 265-290°C to obtain a gram weight of 200g / m2 ;

[0033] The preparation method of the colored polyester masterbatch is:

[0034] (1) Graphite powder, antimony sulfide, stannous chloride pentahydrate, deionized water, and ethylene glycol were mixed in a mass ratio of 11:0.8:1.2:6:4, ground at 80°C for 5 hours, heated to 220°C, dried for 14 hours, and then calcined at 550°C for 6 hours to obtain antimony-tin-doped graphite powder; the grinding speed was 500 rpm, and the mass ratio of the grinding ball to the mass of the silicon graphite powder was 10:1;

[0035] (2) by weight, 7 parts of antimony-tin-doped graphite powder, 7 parts of iron oxide green, 12 parts of phthalocyanine green, 12 parts of chromium oxide green, 30 parts of polyvinyl pyrrolidone, 12 parts of sodium lignin sulfonate, 6 parts of thickener, 3 parts of defoamer, 5 parts of ethylene glycol, and 60 parts of deionized water were stirred and dispersed uniformly, injected into a ceramic nano-grinder for vacuum grinding, and the grinding was stopped when the particle size reached 200 nm to obtain a color paste;

[0036] (3) mixing the color paste and polyester chips in a mass ratio of 1:5, kneading at 170-230° C., and then extruding and granulating at 190-280° C. and a rotation speed of 120-380 rpm to obtain a colored resin masterbatch;

[0037] The preparation method of the thermal insulation aerogel film is as follows: antimony-tin-doped graphite powder and concentrated sulfuric acid are mixed at a ratio of 4 g:40 mL, stirred continuously in a water bath at 80° C. for 4 h, filtered and washed repeatedly with deionized water until the pH of the supernatant is 5.5, and then freeze-dried to obtain acidified antimony-tin-doped graphite powder; ethyl orthosilicate, anhydrous ethanol, deionized water, N,N-dimethylformamide, and oxalic acid are mixed at a molar ratio of 1:8:4:1.5:8×10 -5 Mix, add 1 / 2 of the acidified antimony-tin-doped graphite powder in a ratio of 2g:10mL, mix evenly, soak the fabric therein, soak for 12 hours, adjust the pH to 8 with ammonia water with pH=12, let stand at 50°C for 24 hours, take out the fabric, replace the anhydrous ethanol with deionized water, continue to soak it in deionized water, add the remaining 1 / 2 of the acidified antimony-tin-doped graphite powder, let stand for 24 hours, take out, and obtain it by freeze-drying.

[0038] Example 3

[0039] A multi-layer composite infrared shielding fabric based on graphite powder, comprising a shielding fabric and a heat-insulating aerogel film, wherein the shielding fabric is made by melt spinning and weaving colored polyester masterbatch at 265-290°C to obtain a gram weight of 180-220 g / m 2 ;

[0040] The preparation method of the colored polyester masterbatch is:

[0041] (1) Graphite powder, antimony sulfide, stannous chloride pentahydrate, deionized water, and ethylene glycol were mixed in a mass ratio of 12:1:2:6:4, ground at 80°C for 5 hours, heated to 220°C, dried for 16 hours, and then calcined at 550°C for 6 hours to obtain antimony-tin-doped graphite powder; the grinding speed was 500 rpm, and the mass ratio of the grinding ball to the mass of the silicon graphite powder was 10:1;

[0042] (2) By weight, 10 parts of antimony-tin-doped graphite powder, 10 parts of iron oxide green, 15 parts of phthalocyanine green, 15 parts of chromium oxide green, 40 parts of polyvinyl pyrrolidone, 15 parts of sodium lignin sulfonate, 8 parts of thickener, 5 parts of defoamer, 8 parts of ethylene glycol, and 60 parts of deionized water were stirred and dispersed uniformly, injected into a ceramic nano-grinder for vacuum grinding, and the grinding was stopped when the particle size reached 200 nm to obtain a color paste;

[0043] (3) mixing the color paste and polyester chips in a mass ratio of 1:5, kneading at 170-230° C., and then extruding and granulating at 190-280° C. and a rotation speed of 120-380 rpm to obtain a colored resin masterbatch;

[0044] The preparation method of the thermal insulation aerogel film is as follows: antimony-doped tin graphite powder and concentrated sulfuric acid are mixed at a ratio of 5 g:50 mL, stirred continuously in a water bath at 80° C. for 4 h, filtered and washed repeatedly with deionized water until the pH of the supernatant is 5.5, and then freeze-dried to obtain acidified antimony-doped tin graphite powder; ethyl orthosilicate, anhydrous ethanol, deionized water, N,N-dimethylformamide, and oxalic acid are mixed at a molar ratio of 1:10:5:2:8×10 -5 Mix, add 1 / 2 of the acidified antimony-tin-doped graphite powder in a ratio of 3g:10mL, mix evenly, soak the fabric in it, soak for 12 hours, adjust the pH to 8 with ammonia water with pH=12, let it stand at 50°C for 24 hours, take out the fabric, replace the anhydrous ethanol with deionized water, continue to soak it in deionized water, add the remaining 1 / 2 of the acidified antimony-tin-doped graphite powder, let it stand for 24 hours, take it out, and obtain it through freeze-drying.

[0045] Comparative Example 1

[0046] The difference between Comparative Example 1 and Example 1 is that antimony sulfide is not added in the preparation of antimony-tin-doped graphite powder, and the remaining steps are the same as Example 1.

[0047] Comparative Example 2

[0048] The difference between Comparative Example 2 and Example 1 is that in the preparation of antimony-tin-doped graphite powder, stannous chloride pentahydrate is not added, and the remaining steps are the same as Example 1.

[0049] Comparative Example 3

[0050] The difference between Comparative Example 3 and Example 1 is that there is no thermal insulation aerogel film, and the remaining steps are the same as Example 1.

[0051] Comparative Example 4

[0052] The difference between Comparative Example 4 and Example 1 is that no antimony-tin-doped graphite powder is added during the preparation of the thermal insulation aerogel film, and the remaining steps are the same as Example 1.

[0053] Comparative Example 5

[0054] The difference between Comparative Example 5 and Example 1 is that the remaining 1 / 2 of the antimony-tin-doped graphite powder is not added during the preparation of the thermal insulation aerogel film, and the remaining steps are the same as those of Example 1.

[0055] Comparative Example 6

[0056] The difference between Comparative Example 6 and Example 1 is that no antimony-tin-doped graphite powder is added to the color paste, and the remaining steps are the same as Example 1.

[0057] The infrared emissivity data of the product are shown in Table 1. The infrared emissivity of the stealth fabric prepared by the present invention is tested using an IR-I infrared emissivity measuring instrument developed by the Shanghai Institute of Technical Physics, Chinese Academy of Sciences. The results are shown in Table 1.

[0058] Table 1 Emissivity of the obtained samples in the wavelength range of 8-14 μm

[0059] Emissivity in the wavelength range 8-14μm Example 1 0.62 Example 2 0.56 Example 3 0.54 Comparative Example 1 0.68 Comparative Example 2 0.66 Comparative Example 3 0.74 Comparative Example 4 0.70 Comparative Example 5 0.64 Comparative Example 6 0.69

[0060] From the comparison of the experimental data of Examples 1 to 3, it can be found that the present invention uses low infrared reflectivity dyes and shielding fillers to optimize and compound to a certain concentration of color paste, and the content of shielding fillers in polyester, polyester and aerogel, and aerogel is continuously adjusted to a suitable ratio, which can absorb far infrared rays in a certain wavelength range to the maximum extent, so that the far infrared emissivity is effectively reduced, and can be used for military stealth clothing to expand the use of fabrics; from the comparison of the experimental data of Comparative Examples 1, 2, and 6 with Example 1, it can be found that the present invention improves the far infrared absorption and shielding effects of the powder and reduces the infrared reflection effect by doping graphite powder with antimony and tin, thereby promoting the optimization of the far infrared shielding effect of the fabric; from the comparison of the experimental data of Comparative Examples 3, 4, and 5 with Example 1, it can be found that the present invention constructs a heat-insulating aerogel film by shielding fillers and silica sol, and the two work together to improve the heat insulation performance of the aerogel film, and the heat of the target created by the present invention will not be transferred to the outside, which can effectively attenuate the far infrared energy emitted by the human body itself. After the night test of the thermal infrared imager, the human body image of the thermal imager disappears after the human body is camouflaged, further enhancing the thermal infrared camouflage effect of the fabric.

[0061] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A multi-layer composite infrared shielding fabric based on graphite powder, comprising a shielding fabric and a thermal insulation aerogel film, characterized in that: The shielding fabric is made by melt spinning and weaving colored polyester masterbatch at 265-290°C; The preparation method of the colored polyester masterbatch is: (1) Graphite powder, antimony sulfide, stannous chloride pentahydrate, deionized water, and ethylene glycol are mixed in a mass ratio of 10-12:0.5-1:0.5-2:6:4, ground at 80°C for 4-5 hours, heated to 160-220°C, dried for 10-16 hours, and then calcined at 550°C for 4-6 hours to obtain antimony-tin-doped graphite powder; (2) by weight, 5 to 10 parts of antimony-tin-doped graphite powder, 5 to 10 parts of iron oxide green, 10 to 15 parts of phthalocyanine green, 10 to 15 parts of chromium oxide green, 20 to 40 parts of polyvinyl pyrrolidone, 10 to 15 parts of sodium lignin sulfonate, 2 to 8 parts of thickener, 1 to 5 parts of defoamer, 3 to 8 parts of ethylene glycol, and 50 to 60 parts of deionized water are stirred and dispersed uniformly, injected into a ceramic nano-grinder for vacuum grinding, and the grinding is stopped when the particle size reaches 200 nm to obtain a color paste; (3) The color paste and polyester chips are mixed in a mass ratio of 1:3-11, kneaded at 170-230° C., and then extruded and granulated at 190-280° C. and a rotation speed of 120-380 rpm to obtain a colored resin masterbatch.

2. The multi-layer composite infrared shielding fabric based on graphite powder according to claim 1, characterized in that: The grinding speed in step (1) is 100 rpm-500 rpm, and the mass ratio of the grinding balls to the mass of the silicon graphite powder is (5-20):

1.

3. The multi-layer composite infrared shielding fabric based on graphite powder according to claim 2, characterized in that: The grinding jars and grinding balls used are made of the same material, stainless steel, hard steel, zirconium oxide ceramic, corundum or agate.

4. The multi-layer composite infrared shielding fabric based on graphite powder according to claim 1, characterized in that: The thickener in step (2) is an acrylate polymer, and the defoamer is a non-ionic multiphase silicone polymer.

5. The multi-layer composite infrared shielding fabric based on graphite powder according to claim 1, characterized in that: The shielding fabric has a grammage of 180 to 220 g / m 2 .

6. The multi-layer composite infrared shielding fabric based on graphite powder according to claim 1, characterized in that: The preparation method of the thermal insulation aerogel film is as follows: mixing antimony-tin-doped graphite powder and concentrated sulfuric acid, heating and acidifying, repeatedly filtering and washing with deionized water until the pH of the supernatant is 5-6, and then freeze-drying to obtain the acidified antimony-tin-doped graphite powder; mixing ethyl orthosilicate, anhydrous ethanol, deionized water, N,N-dimethylformamide, and oxalic acid, adding 1 / 2 of the acidified antimony-tin-doped graphite powder in a ratio of 1-3g:10mL, mixing evenly, and soaking the fabric therein. After soaking for 12 hours, adjust the pH to 8 with ammonia water with pH = 12, let it stand at 50°C for 24 hours, take out the fabric, replace the anhydrous ethanol with deionized water, continue to soak in deionized water, add the remaining 1 / 2 acidified antimony-tin-doped graphite powder, let it stand for 24 hours, take it out, and obtain it through freeze-drying.

7. The multi-layer composite infrared shielding fabric based on graphite powder according to claim 6, characterized in that: The ratio of the antimony-tin-doped graphite powder to concentrated sulfuric acid is (3-5) g: (30-50) mL.

8. The multi-layer composite infrared shielding fabric based on graphite powder according to claim 6, characterized in that: The molar ratio of the tetraethyl orthosilicate, anhydrous ethanol, deionized water, N,N-dimethylformamide and oxalic acid is 1:6-10:3-5:1-2:8×10 -5 .